`It`s a whole new ball game`: thirty years of the English Premier League - Parnell, D.; Rookwood, J.; Bond, A.; Widdop, P.; Ludvigsen, J. A. L. (Soccer & Society, 2022)
The 30-year history of the EPL has proved extremely eventful, insightful, and controversial. Indeed, scholars have been responsive to this, and academic work on the social, financial, political, and cultural facets or impacts of the EPL has subsequently grown considerably. However, we - the guest editors of this special issue - would also argue that the 30th anniversary of the EPL requires and, in fact, provides an important space for reflection. Moreover, it also allows for attempts to tentatively envisage what the future might hold for the EPL, the communities surrounding the clubs, and indeed, English and world football more broadly. As such, this special issue seeks to do precisely this. Collectively, this special issue aims to further the understanding of the EPL`s developments, the current state of play and, importantly, the future challenges that lie ahead - essential for a league, closely followed by millions of fans and commentators each week, both domestically and transnationally. The individual papers in this special issue explore the EPL`s past, present, and future.